If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x^2-1x-4=0
a = 3; b = -1; c = -4;
Δ = b2-4ac
Δ = -12-4·3·(-4)
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:x_{1}=\frac{-b-\sqrt{\Delta}}{2a}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}\sqrt{\Delta}=\sqrt{49}=7x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-1)-7}{2*3}=\frac{-6}{6} =-1x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-1)+7}{2*3}=\frac{8}{6} =1+1/3
| 192=6x+6(5x-16) | | 260/52=x | | 3x+9-x-2=17 | | (w/7)+4=6 | | 3x+2(7x+4)=195 | | 9m-4(m+1)=-(3m-20 | | 8=n-41/2 | | 6/7u-8/3=-3/2 | | 5x+3x2=2 | | (4-7x)5+4x=175 | | -66=-6v | | 7/5x-1/3=1/6x-18 | | 9-4(1+4v)=-84 | | -161=-4(-1+6x)+3 | | 2s-8=s+6 | | 11/16=n+7/9 | | -147=7(-4n+3) | | 4x+5(2x-3)=69 | | -9+x/7=-3 | | 0.8x−2=0.48x+6 | | (17+x)2+6x=90 | | (8-3x)5+5x=60 | | n/4=-2.7 | | (x(4-3x)+4(x^2+1))/x^2-4=0 | | 45x-33x+19=25+17 | | 12m+6=15m-3 | | 2x=(90/4) | | 6m+3=29; | | (7-x)5+7x=73 | | 10=-4p-6p | | 6y+1=3y+28 | | 15/18y+1=−6/18y+10/18 |